2020
DOI: 10.1103/physrevlett.124.112301
|View full text |Cite
|
Sign up to set email alerts
|

Multigluon Correlations and Evidence of Saturation from Dijet Measurements at an Electron-Ion Collider

Abstract: We study inclusive and diffractive dijet production in electron-proton and electron-nucleus collisions within the Color Glass Condensate effective field theory. We compute dijet cross sections differentially in both mean dijet transverse momentum P and recoil momentum ∆, as well as the anisotropy in the relative angle between P and ∆. We use the nonlinear Gaussian approximation to compute multiparticle correlators for general small x kinematics, employing running coupling Balitsky-Kovchegov evolution to determ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 81 publications
1
68
0
Order By: Relevance
“…In order to JHEP12(2020)181 make our ITMD/CGC comparison feasible and clear, we shall restrict our analysis to the forward quark (qq) dijet production, and work within the Gaussian truncation of JIMWLK evolution and large-N c limit, for which the CGC expression is less complicated and can be evaluated directly (indeed, as we will see below, the two expressions then differ only in their hard factors). In this regard, we note that genuine-twist corrections were also analyzed recently in the context of dijet production in deep-inelastic scattering [21], using the same approximation but keeping finite N c corrections.…”
Section: Introductionmentioning
confidence: 72%
“…In order to JHEP12(2020)181 make our ITMD/CGC comparison feasible and clear, we shall restrict our analysis to the forward quark (qq) dijet production, and work within the Gaussian truncation of JIMWLK evolution and large-N c limit, for which the CGC expression is less complicated and can be evaluated directly (indeed, as we will see below, the two expressions then differ only in their hard factors). In this regard, we note that genuine-twist corrections were also analyzed recently in the context of dijet production in deep-inelastic scattering [21], using the same approximation but keeping finite N c corrections.…”
Section: Introductionmentioning
confidence: 72%
“…Along the same lines, taking into account the multigluon correlations inside nuclear targets at small x in Ref. [16] the elliptic modulation of diffractive dijets was investigated and it was shown that saturation effects are significant when looking at the nuclear modification of the ratio between the differential inclusive and diffractive dijet cross sections. Authors of Ref.…”
Section: Provides a Direct Measurement Of The Saturation Scale As A Fmentioning
confidence: 99%
“…Much of the discussion on azimuthal angle correlations at small x in the CGC and related frameworks has been restricted to dijet/dihadron production in p(d) + A collisions [41,[43][44][45][46][47][48][49][50][51][52][53][54][55]. Similar studies have been performed for the case of e + A scattering for the production of dijets/dihadrons [42,[56][57][58] and trijets 3 [61]. We will explore here such correlations between the observed photon and quark in the context of e + A collisions at small x.…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, in the case of photon+dijet production, the quantum expectation value for the process depends on two-point "dipole" and four-point "quadrupole" correlators [38]. The former is accessed in fully inclusive DIS while extraction of the latter requires more differential measurements such as inclusive dijet production [41,42] and the photon+dijet process discussed in [38].…”
Section: Introductionmentioning
confidence: 99%